2015
DOI: 10.1590/s0100-736x2015001200003
|View full text |Cite
|
Sign up to set email alerts
|

Detecção de Brucella abortus em linfonodos de búfalas (Bubalus bubalis) em diferentes fases da gestação

Abstract: The objective of this study was to detect Brucella abortus in lymph nodes of buffaloes as well as to describe the lesions caused. Nineteen buffalo cows in various stages of pregnancy, serologically positive for brucellosis and subjected to culling were used. Fetal age was determined by ultrasound examination and the size of fetuses was measured at necropsy. Fragments of lymph nodes were collected for histopathology and qPCR. The detection of B. abortus DNA in the lymph nodes was checked from the fourth month o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Chronic suppurative endometritis with areas of fibrosis and the presence of numerous basophilic coccoid bacterial colonies on the endometrial ulcerated surface is also observed. In the lymph nodes, congestion, edema, fibrin, infiltration by neutrophils, histiocytes and plasma cells are observed, which characterize regional lymphadenitis (Sousa et al 2015b). In buffalo fetuses, liver with small foci of lymphocytic infiltrates distributed throughout the parenchyma, with mild to moderate injury, diffuse vacuolization of hepatocytes, kidney and spleen congestion, congestion, edema and fibrin in the lymph nodes are detected (Sousa et al 2015a).…”
Section: Anatomopathological Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chronic suppurative endometritis with areas of fibrosis and the presence of numerous basophilic coccoid bacterial colonies on the endometrial ulcerated surface is also observed. In the lymph nodes, congestion, edema, fibrin, infiltration by neutrophils, histiocytes and plasma cells are observed, which characterize regional lymphadenitis (Sousa et al 2015b). In buffalo fetuses, liver with small foci of lymphocytic infiltrates distributed throughout the parenchyma, with mild to moderate injury, diffuse vacuolization of hepatocytes, kidney and spleen congestion, congestion, edema and fibrin in the lymph nodes are detected (Sousa et al 2015a).…”
Section: Anatomopathological Findingsmentioning
confidence: 99%
“…Sousa 2 , Felipe M. Salvarani 2 , Henrique A. Bomjardim 2 , Marilene F. Brito 3 and José D. Barbosa 2 * with fibrinous suppurative necrotic placentitis (Sousa et al 2015a). Brucellosis has been diagnosed in water buffaloes from Egypt (Gentile 1957, Menshawy et al 2014, Italy (Guarino et al 2001), Trinidad and Tobago (Fosgate et al 2002), Pakistan (Nasir et al 2004), Argentina (Konrad et al 2013) and Brazil (Ogassawara et al 1969, Santa Rosa et al 1969, Láu & Singh 1985, Bastianetto et al 2005, Silva et al 2014a, Sousa et al 2015a, 2015b.…”
Section: Brucellosis In Water Buffaloesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, developed countries in Latin America, Southern Europe, Africa, South and Southeast Asia, and the Middle East, especially in the rural areas, where livestock rearing and production of dairy products and by-products is crucial for family income [2,7,56,[75][76][77][78][79][80].…”
Section: Brucellosismentioning
confidence: 99%